2015
DOI: 10.1007/s10803-015-2600-9
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Social Competence Using a Randomized Trial of a Theatre Intervention for Children with Autism Spectrum Disorder

Abstract: The efficacy of a peer-mediated, theatre-based intervention on social competence in participants with autism spectrum disorder (ASD) was tested. Thirty 8-to-14 year-olds with ASD were randomly assigned to the treatment (n = 17) or a wait-list control (n = 13) group. Immediately after treatment, group effects were seen on social ability (d = .77), communication symptoms (d = −.86), group play with toys in the company of peers (d = .77), immediate memory for faces as measured by neuropsychological (d = .75) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
137
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(144 citation statements)
references
References 82 publications
4
137
0
3
Order By: Relevance
“…For instance, Corbett showed efficacy on social competence of a theater-based intervention with young, trained peer actors [75]. Barber demonstrated efficacy of the Stay Play Talk procedure: a neurotypical child was paired with a child with ASD and was taught to stay, play and talk with him during 20-min weekly sessions about communication skills [76].…”
Section: ) Study Of the Impact Of An Implicit Social Skills Trainingmentioning
confidence: 99%
“…For instance, Corbett showed efficacy on social competence of a theater-based intervention with young, trained peer actors [75]. Barber demonstrated efficacy of the Stay Play Talk procedure: a neurotypical child was paired with a child with ASD and was taught to stay, play and talk with him during 20-min weekly sessions about communication skills [76].…”
Section: ) Study Of the Impact Of An Implicit Social Skills Trainingmentioning
confidence: 99%
“…For example, studies we have conducted have shown that SENSE Theatre ® , a theatrical intervention program in which youth with ASD learn a variety of acting techniques with peer actors who model communication and behavioral skills, contributes to significant changes in participants' social competence, communication, cognition, and interaction skills [27][28][29][30]. Whether people with autism are onstage or in the audience, published and anecdotal reports [21,28] suggest that the theater provides a distinctive setting where they may thrive. The supportive context, active role-playing, and dynamic learning environment of the theater foster the development of key social skills that children with autism most need to learn.…”
mentioning
confidence: 99%
“…Engaging in singing instead of vocal stereotypy may allow individuals with ASD to be involved in several related social activities, such as choir, glee club, or musical theater. Participation in such groups would provide more opportunities for children with ASD to develop singing or performing skills as well as increase occasions for social interaction and improve social competence (Corbett et al, ; Corbett et al, ), which may in turn facilitate the formation of friendships. For example, Donald T., the first individual diagnosed with ASD, was reported to display frequent and various forms of vocal stereotypy across his youth (Kanner, ), and this later developed into membership in his college a capella choir (Donvan & Zucker, ).…”
Section: Discussionmentioning
confidence: 99%